Deciphering genotype × environment interactions by AMMI method for yield and component traits in linseed (Linum usitatissimum L.): DECIPHERING GENOTYPE × ENVIRONMENT INTERACTIONS BY AMMI METHOD FOR YIELD IN LINSEED - MITHLESH KUMAR; MANUBHAI PATEL; RAVINDRASINGH CHAUHAN; CHANDRESH TANK; SATYANARAYAN SOLANKI (Journal of Oilseeds Research, 2020)
In the present study, additive main effects and multiplicative interactions (AMMI) biplot analyses were used to identify stable genotypes for number of bolls/plant, seeds/boll, seed yield/plant and oil content to dissect GEI in linseed. Trials were conducted in randomized complete block design (RCBD) with two replications over three consecutive years, 2016-17, 2017-18 and 2018-19. ANOVAanalysis revealed genotype and G×E interaction effects contributed significant sum of square for number of bolls/plant (96.50% and 0.30%); seeds/boll (74.01% and 4.24%); seed yield/ plant (94.06% and 1.57% ) and oil content (92.06% mainly genotype effect). The dissection of GE interaction for all the traits was mostly explained by the first and second principal component axis (IPCA1 and IPCA2). Results of genotype's stability in AMMI1 and AMMI2 biplot analyses showed differential response with some exceptions that indicated the different sets of genes and effect of environment on the cumulative expression of traits under study. The AMMI2 biplot graphs showed similar environmental response for number of bolls/plant, seeds/boll, seed yield/plant and oil content as in case of AMMI1 analysis. The Simultaneous stability index (SSI) statistic fully corresponded with the results of the AMMI1 biplot models for all the traits of top ranked genotypes across the environments. The linseed genotypes identified for yield and stability could be advocated for varietal recommendation and further use in hybridization program in semi-arid conditions.